Outcomes of pregnancies complicated by diabetes. (7th June 2011) - Oniya, O; Mackay, V; Gallagher, A; Ledingham, M; Gibson, J
Abstract : Background: Diabetes remains the most common pre-existing medical disorder complicating pregnancy in the UK. In 1989 the St Vincent Declaration suggested that outcomes of pregnancy should be similar in women with and without diabetes.1 Method: Retrospective study using maternal records. All women were managed in a multidisciplinary clinic. Scottish Intercollegiate guideline recommendations were followed for their care.2 Objective: To analyse the outcomes of pregnancy in the diabetic population over a 2 year period. Results: 103 cases were identified. Gestational diabetes n=45, Type 1 diabetes n=50 and Type 2 diabetes n=8. Median age was 29 years. There were 102 live births and only 1 stillbirth at 24 weeks. Caesarean section rate was 50% (25% emergency and 25% elective). Vaginal delivery rate was 38% and instrumental delivery rate 12%. There were eight growth restricted infants and 47% had birth weights greater than the 90th centile. 30% required SCBU admission. There was 1 case of severe shoulder Dystocia and 1 severe Hypoxic Ischemic encephalopathy. Congenital malformations included 1 renal anomalie, 1 congenitally short femur and 1 polydactyly (rate 2.9%). Conclusion: The congenital anomaly and perinatal mortality were similar to that of normal controls. Caesarean section rate and neonatal morbidity were high compared to the background rate. Optimal outcome is possible in diabetic pregnancies with good glycaemic control in women managed in a multidisciplinary clinic.